2013
DOI: 10.1074/jbc.m112.408245
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Membrane-tethered Mucin 3 (MUC3) Expression by a Tetrameric Branched Peptide with a Conserved TFLK Motif Inhibits Bacteria Adherence*

Abstract: Background: A tetrameric branched peptide (BP) containing a TFLK motif was designed to induce MUC3 expression and inhibit bacteria adherence. Results: TFLK-containing 10-mer BP induced MUC3 expression and dramatically inhibited bacteria adherence to the HT-29-Gal cells. Conclusion: This peptide acts through transcriptional mechanisms.Significance: This peptide has potential therapeutic value against gastrointestinal infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Pan et al expressed synthetic tetrameric-branched peptide that enhanced the expression of Mucin 3 (25). They found that Mucin 3 interacted with EPEC and EHEC and reduced their binding to epithelial cells.…”
Section: Enteropathogenic E Coli (Epec)mentioning
confidence: 99%
“…Pan et al expressed synthetic tetrameric-branched peptide that enhanced the expression of Mucin 3 (25). They found that Mucin 3 interacted with EPEC and EHEC and reduced their binding to epithelial cells.…”
Section: Enteropathogenic E Coli (Epec)mentioning
confidence: 99%
“…The pGL3-Basic vector containing the miR-200b-a-429 promoter (Ϫ158 to ϩ19 bp) and two E-box sites (CACCTG) served as a wild-type construct for the generation of the miR-200b-a-429-Luc construct, which harbors mutations in the two E-box sites (CACCGG) via PCRbased site-directed mutagenesis. Transfection of the luciferase reporters with different miR-200 promoters and luciferase assays were performed as described in our previous report (19).…”
Section: Methodsmentioning
confidence: 99%
“…It is part of a tandem duplication involving MUC3A, and MUC3B is expressed exclusively in the small intestine and colon (Pratt et al 2000;Kyo et al 2001). Variants of MUC3A have been associated with inflammatory bowel disease, and up-regulation of MUC3 inhibited adherence of pathogenic E. coli in human intestinal cells (Pan et al 2013). The CHM1 version of MUC3B contains four copies of the tandem repeat.…”
Section: Gene Contentmentioning
confidence: 99%